2018
DOI: 10.1039/c8nr08376b
|View full text |Cite
|
Sign up to set email alerts
|

3D characterization of heat-induced morphological changes of Au nanostars by fast in situ electron tomography

Abstract: The thermal reshaping and its influence on the plasmonic properties of gold nanostars are investigated using a combination of in situ tomography and a state-of-the-art fast acquisition approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
130
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 67 publications
(132 citation statements)
references
References 40 publications
1
130
0
1
Order By: Relevance
“…Other indirect evidence of alloy formation is provided by 2D energy‐dispersive X‐ray (EDX) projection images. However, 2D TEM projection images of 3D objects can be very misleading and are not necessarily representative for the real 3D composition …”
Section: Introductionmentioning
confidence: 99%
“…Other indirect evidence of alloy formation is provided by 2D energy‐dispersive X‐ray (EDX) projection images. However, 2D TEM projection images of 3D objects can be very misleading and are not necessarily representative for the real 3D composition …”
Section: Introductionmentioning
confidence: 99%
“…This result is similar to recent studies based on photothermal reshaping, 36 where it is shown that anisotropic particles evolve towards a spherical morphology due to the higher mobility and lower melting point of atoms at corners or tips. 37 Several aliquots were extracted at different times during the heating process and cooled down to quench reshaping. Each aliquot was further partitioned into three equal volumes and MBA, ABT, or 4-acetylaminobenzenthiol (AABT) were then added.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] Alternatively, electron tomography (ET) techniques enable researchers to reconstruct three-dimensional images of nanoparticles using two-dimensional projection TEM/ STEM images and eventually determine the functionality of many structures. [17][18][19][20][21][22] Currently, following the developments of electron sources, spectrometers and spherical-aberration correctors, applications of electron microscopy in semiconductors, materials science, and biological science are booming. [23][24][25][26] Moreover, the newly invented direct electron detection camera makes it possible to work with both high spatial and temporal resolution at the same time, laying a solid foundation to record the structural evolution of nanoparticles in response to mechanical, thermal, and/or chemical stimulations.…”
Section: Introductionmentioning
confidence: 99%